Strategi Konselor Adiksi Menangani Perilaku Penyalahgunaan Narkoba Melalui Terapi Religius - Yuniarti, Hanifah Dwi; Fajar, Dadang Ahmad; Effendi, Dudy Imanuddin (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2024)
The purpose of this study was to analyze the methods, planning, support systems, and results of addiction counselor strategies in dealing with drug abuse behavior through religious therapy at the Grapiks Foundation. This research uses a qualitative approach that produces data from the object of research with descriptive methods through interviews, observations, and documentation. The results of this study indicate that the religious therapy method used in dealing with drug abuse behavior at the Grapiks Foundation uses the narcotics religious method with 7 stages, namely intention, repentance, prayer, endeavor, tawakal, gratitude, and istiqamah. Addiction counselor planning is socialization, consultation, identification, motivation, selection, acceptance, assessment, and intervention plan. System support in planning, namely personnel and program management. The results of this religious therapy can be felt by victims of drug abuse, namely a healthy physical condition and can be seen from their behavior that is much better.